Mechanical Properties of Cement Mortar Made with Black Tea Waste Ash as a Partial Replacement of Cement - Mohammed Nasr; Zaid Hasan; Mohammed Abed (Engineering and Technology Journal, 2019)
Environmental pollution and the relatively high cost of waste disposal has been a major focus for scientists around the world, leading researchers to find a solution to reuse waste materials in different applications. Iraqi people consume hundreds of tons of black tea each year, which produce a large quantity of the used tea, leaves as waste. These large quantities go to landfills without any benefit or recycling. Additionally, landfills are considered one of the biggest crisis facing the Iraqi government. Therefore, this study aims to recycle the black tea waste ash (BTWA) by utilizing it as a partial replacement of cement. Cement mortar mixes containing five replacement levels of cement with BTWA (0%, 2.5%, 5%, 7.5% and 10% by weight) were carried out. The compressive strength and flexural strength tests were adopted to show the effect of BTWA on mechanical properties of cement mortar. The flow rate of fresh mortar was also measured. Results indicated that, up to 7.5% replacement, the compressive strength values were improved. For 10% replacement, the compressive strength values were equal to that for control specimens. In contrast, the BTWA had a negative impact on the flexure strength of mortar at replacement levels 5%, 7.5% and10%. For 2.5% substitution, however, the flexure strength was enhanced slightly (about 2%).